Circling COVID: Making in the Time of a Pandemic - Wenzel, Abra (Anthropologica, 2021)
The following is an account of some current Indigenous artistic trends and responses during the COVID‑19 pandemic. The pandemic has resulted in Indigenous artists adapting social media to maintain COVIDdisrupted knowledge networks about traditional making. In so doing, they have reimagined how to continue links within and beyond their own cultural communities. Art has become both an outlet and a connection to neighbours, friends, and strangers across geographic boundaries. Indigenous textile artists are refashioning their art and materials to maintain and reflect contemporary Indigenous issues and values that emphasize their community and reflect survivance, all while safely at a distance. The artists highlighted and discussed in this article include Dene, Métis, and Inuvialuit women with whom I have worked and who have contributed to my research in the Northwest Territories (NWT), as well as other Indigenous artists from across North America well known for their creative work. Because the coronavirus has all but eliminated non-essential travel to the NWT, the information that is presented has been developed through online exchanges with these women and by observing the artists’ public social media accounts over the course of six months.